Genome-wide identification and functional characterization of wheat Brassinazole-resistant transcription factors in response to abiotic stresses and stripe rust infection - Zhang, Peng; Yan, Hanwen; Liu, Yu; Chai, Yi (Frontiers in Plant Science, 2023)
Brassinazole-resistant (BZR) transcription factors (TFs) are key players in brassinolides (BRs) signaling pathway, which widely involved in regulating plant growth and development, as well as in plant responding to a variety stresses. Despite their critical roles, little is known about BZR TFs in wheat. In this study, we performed genome-wide analysis of BZR gene family from wheat genome, and finally identified 20 TaBZRs. Based on the phylogenetic relationships of TaBZR and BZRs from rice and Arabidopsis, all BZR genes were clustered into four groups. The intron-exon structural patterns and conserved protein motifs of TaBZRs were analyzed and showed high group specificity. According to the published transcriptome data, TaBZR5, 7, and 9 were significantly induced under salt, drought treatment, and stripe rust infection. Furthermore, TaBZR9 might play as a hub in wheat in response to various biotic and abiotic conditions. While the expression of TaBZR16 was down-regulated in heat and drought treatments, it can be concluded that BZR genes in wheat play different roles in response to various stresses. The results of this study will lay a foundation for further in-depth functional studies of TaBZRs and will provide information for the breeding and genetic improvement of wheat against drought and salt stresses.